TERMIZ RAILWAY - ECONOMIC BASIS FOR POLITICAL INTERESTS - KHIDIROV HOLMAT DJURAEVICH (International Journal of Innovations in Engineering Research and Technology, 2021)
This article shows that one of the most powerful vehicles in the Surkhandarya oasis is rail transport. The most important advantage of rail transport is that it has the capacity to carry a lot of cargo and works at the same rate throughout the year. There was no mention of the specifics of the construction of this transport network in our oasis.